Effects of different anti-caries agents on microhardness and superficial microstructure of irradiated permanent dentin: an in vitro study - LiLing Wu; Kun Geng; QingPing Gao (BMC, 2019)
Abstract Background To compare different anti-caries agents on microhardness and micromorphology of irradiated permanent dentin in vitro, and try to find the most effective agent to prevent radiation-dentin-destruction. Methods A total of 120 dentin samples were prepared from 60 human teeth and randomly divided into 8 groups (n = 15), [ (1)] blank control [2]; irradiation control [3]; irradiation+ fluoride [4]; irradiation+ casein phosphate polypeptide-amorphous calcium phosphate (CPP-ACP) [5]; irradiation+ CPP-ACP+ fluoride [6]; irradiation+ infiltration resin [7]; irradiation+ infiltration resin+ fluoride [8]; irradiation+ infiltration resin+ CPP-ACP. Seven samples of each groups were chosen randomly for microhardness test and eight for scanning electron microscope observation. Results: A decrease of microhardness (P < 0.05) and an obvious morphological change were presented on dentin surface after radiotherapy. After applications of anti-caries agents, the morphological destructions were effectively restored. The infiltration resin plus fluoride group (56.00 ± 4.02 Kg/mm2), infiltration resin plus CPP-ACP group (56.05 ± 3.69 Kg/mm2), infiltration resin group (54.70 ± 4.42Kg/mm2) and CPP-ACP plus fluoride group (53.84 ± 6.23Kg/mm2) had the highest dentin microhardness value after radiotherapy, and no statistically significant difference were found between them. Conclusions Infiltration resin, CPP-ACP, fluoride and their pairwise combination can effectively prevent radiation-dentin-destruction. Among them, infiltration resin with CPP-ACP, infiltration resin with fluoride, CPP-ACP with fluoride, and infiltration resin have the most protective effects on irradiation-dentin-destructions.